2018
DOI: 10.1021/acs.jafc.8b03452
|View full text |Cite
|
Sign up to set email alerts
|

Cucumber and Tomato Volatiles: Influence on Attraction in the Melon FlyZeugodacus cucurbitate(Diptera: Tephritidae)

Abstract: The main hosts of the melon fly Zeugodacus cucurbitate are cultivated and wild cucurbitaceous plants. In eastern Africa, the melon fly is a major pest of the Solanaceae plant Solanum lycopersicum (tomato). We hypothesized that shared species-specific volatiles may play a role in host attraction. We tested this hypothesis by comparing the olfactory responses of the melon fly to Cucumis sativus (cucumber) (Cucurbitaceae) and tomato plant odors in behavioral and electrophysiological assays, followed by chemical a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
22
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 23 publications
(24 citation statements)
references
References 44 publications
2
22
0
Order By: Relevance
“… * Means with different letters for each compound are significantly different from each other (ANOVA followed by SNK post hoc test; P < 0.05, n = 3). DPI, days post infection; RI Calculated , retention index relative to C 8 –C 31 n -alkanes of an HP-5 MS column; RI Literature , retention index obtained from the literature; ND, not detected; BDL, below detection limit. ** Compound whose identity was established based on the comparison of retention time and mass spectra data with an authentic standard. *** Compound identified tentatively based on library data, calculated RI values, and comparison to the literature: (A), (B), (C), (D), (E), (F), (G), (H), and (I) …”
Section: Resultsmentioning
confidence: 99%
“… * Means with different letters for each compound are significantly different from each other (ANOVA followed by SNK post hoc test; P < 0.05, n = 3). DPI, days post infection; RI Calculated , retention index relative to C 8 –C 31 n -alkanes of an HP-5 MS column; RI Literature , retention index obtained from the literature; ND, not detected; BDL, below detection limit. ** Compound whose identity was established based on the comparison of retention time and mass spectra data with an authentic standard. *** Compound identified tentatively based on library data, calculated RI values, and comparison to the literature: (A), (B), (C), (D), (E), (F), (G), (H), and (I) …”
Section: Resultsmentioning
confidence: 99%
“…Each compound detected in the headspace volatiles was quantified using the external calibration method. Due to unavailability of synthetic standard from each reported chemical class, a relative quantification was performed using the linear equation of a monoterpene to quantify compounds with a retention time of less than 16 min (range where monoterpenes are dominant in the headspace volatiles), and the linear equation of a sesquiterpene to quantify compounds with a retention time beyond 16 min, where sesquiterpenes are dominant in the headspace volatiles, and this followed the quantification method used by Njuguna et al 61 . The monoterpene α -pinene and the sesquiterpene α -humulene were run at different concentrations and the linear equations were generated from the calibration curves (Supplementary Fig.…”
Section: Methodsmentioning
confidence: 99%
“…The response of an insect to a given compound is known to occur in dose-dependent manner ( Kihika et al, 2017 ; Njuguna et al, 2018 ). In this study, we showed that females of T. absoluta responded differently to the concentrations of the individual compounds and the blend with and without methyl salicylate against the control.…”
Section: Discussionmentioning
confidence: 99%
“…Three concentrations of each compound were tested in their natural release rate (ng/plant/h) from inoculated tomato plant, then by doubling and halving the amounts of each individual compound. Based on the results, three compounds (α-pinene, 2-carene, and β-phellandrene) were found attractive to females of T. absoluta and were tested in three-component blend at three concentrations against the control and methyl salicylate which was repellent to the females (2.17 ng/μL): (1.86 ng/μL α-pinene, 53.94 ng/μL 2-carene, 74.87 ng/μL β-phellandrene) (blend B1) which was subsequently doubled (blend B2) and diluted to one-half (blend B3) ( Njuguna et al, 2018 ; Kihika et al, 2020 ). In another set of experiment, methyl salicylate (2.17 ng/μL) was tested against non-inoculated tomato plant.…”
Section: Methodsmentioning
confidence: 99%